Buyang Huanwu Decoction Targets SIRT1/VEGF Pathway to Promote Angiogenesis After Cerebral Ischemia/Reperfusion Injury - Zheng, Xia-Wei; Shan, Chun-Shuo; Xu, Qing-Qing; Wang, Yong; Shi, Yi-Hua; Wang, Yan; Zheng, Guo-Qing (Frontiers in Neuroscience, 2018)
Background: Ischemia stroke is known as the major cause of morbidity and mortality. Buyang Huanwu Decoction (BHD), a classical traditional Chinese medicine (TCM) formula, has been used to prevent and treat stoke for hundreds of years. The purpose of present study is to investigate the effects of BHD on angiogenesis in rats after cerebral ischemia/reperfusion (I/R) injury targeting Silent information regulator 1 (SIRT1) / Vascular endothelial growth factor (VEGF) pathway. Methods: The cerebral I/R injury model was induced by middle cerebral artery occlusion (MCAO). Adult Sprague-Dawley rats were randomly divided into five groups: sham group, normal saline (NS) group, BHD group, BHD+EX527 (SIRT1 specific inhibitor) group and NS+EX527 group. Each group was divided into the subgroups according to 1d, 3d, 7d or 14d time-point after cerebral ischemia/reperfusion, respectively. Neurological function score (NFS) was evaluated by the Rogers scale; microvascular density (MVD) in brain tissue around infarction area was observed by immunofluorescence; and the expression of SIRT1 and VEGF was assessed by Western Blot and Quantitative Real-time-PCR. Results: BHD can significantly improve NFS (P<0.05), increase the MVD in the boundary ischemic area (P<0.01) and elevate the expression of protein and mRNA of SIRT1 and VEGF following I/R injury (P<0.01). In contrast, treatment with EX527 reversed the BHD-induced improvements in NFS (P<0.01) and decreased the MVD (P<0.01) and the expression of SIRT1 and VEGF (P<0.05). Conclusion: BHD exerts neuroprotection targeting angiogenesis through the up-regulation of SIRT1/VEGF pathway against cerebral ischemic injury in rats.